Early Outgrowth Cells Release Soluble Endocrine Antifibrotic Factors That Reduce Progressive Organ Fibrosis. (November 2013) - Yuen, Darren A.; Connelly, Kim A.; Zhang, Yanling; Advani, Suzanne L.; Thai, Kerri; Kabir, Golam; Kepecs, David; Spring, Christopher; Smith, Christopher; Batruch, Ihor; Kosanam, Hari; Advani, Andrew; et al.
Abstract Adult bone marrow‐derived cells can improve organ function in chronic disease models, ostensibly by the release of paracrine factors. It has, however, been difficult to reconcile this prevailing paradigm with the lack of cell retention within injured organs and their rapid migration to the reticuloendothelial system. Here, we provide evidence that the salutary antifibrotic effects of bone marrow‐derived early outgrowth cells (EOCs) are more consistent with an endocrine mode of action, demonstrating not only the presence of antifibrotic factors in the plasma of EOC‐treated rats but also that EOC conditioned medium (EOC‐CM) potently attenuates both TGF‐β‐ and angiotensin II‐induced fibroblast collagen production in vitro. To examine the therapeutic relevance of these findings in vivo, 5/6 subtotally nephrectomized rats, a model of chronic kidney and heart failure characterized by progressive fibrosis of both organs, were randomized to receive i.v. injections of EOC‐CM, unconditioned medium, or 106 EOCs. Rats that received unconditioned medium developed severe kidney injury with cardiac diastolic dysfunction. In comparison, EOC‐CM‐treated rats demonstrated substantially improved renal and cardiac function and structure, mimicking the changes found in EOC‐treated animals. Mass spectrometric analysis of EOC‐CM identified proteins that regulate cellular functions implicated in fibrosis. These results indicate that EOCs secrete soluble factor(s) with highly potent antifibrotic activity, that when injected intravenously replicate the salutary effects of the cells themselves. Together, these findings suggest that an endocrine mode of action may underlie the effectiveness of cell therapy in certain settings and portend the possibility for systemic delivery of cell‐free therapy. Stem Cells2013;31:2408–2419